ACCESS SITES TO VASCULAR SYSTEM FOR ENDOVASCULAR ABDOMINAL AORTIC ANEURYSMS REPAIR - Utikal, Petr; Koecher, Martin; Bachleda, Petr; Koutna, Jirina; Drac, Petr; Cerna, Marie (Biomedical papers, 2006)
The authors describe their experience with access sites for endovascular abdominal aortic aneurysm repair in a group of 165 patients treated over a 10-year period.
Keywords: Aorta/Aneurysm/Repair/Endovascular/Access sites/Surgical/Alternative/Percutaneous/Adjunctive procedures